Language Attitudes and Their Implications in Student Characters’ Development - Surahmat, Surahmat; Burhanudin, Muhamad; Prasandha, Diyamon (English Education : English Journal for Teaching and Learning, 2025)
Reputation is an identity that universities continue to strive for. In the digital era, social media is used to achieve this. This article's discussion includes a discourse analysis of how students at Universitas Negeri Semarang use language, along with an explanation of how their language performances and expressions on social media reflect their attitudes and manners. The findings of the study demonstrate that students' utterance or speech patterns vary based on the factors and objectives of their speeches. Adding more, it's said that students of Universitas Negeri Semarang have good language awareness. The methods for preserving the presence of positive student content through the development of language character are also included in this assessment.